Aerobic Exercise Ameliorates Alzheimer’s Disease-Like Pathology by Regulating Hepatic Phagocytosis of Aβ - Qing Wang; Feng-Rui Hu; Xing-Chun Gou; Shan Wang; Nai-Chun Ji (Frontiers in Bioscience-Landmark)
Background: Alzheimer’s disease (AD) is a neurodegenerative disease which significantly and negatively affects families and society. Aerobic exercise serves as a non-pharmacological strategy, potentially safeguarding against cognitive decline and lowering the risk of AD. However, how aerobic exercise ameliorates AD remains unknown. This study investigated the effects of two types of aerobic exercise, including aerobic interval training (AIT) and aerobic continuous training (ACT), on cognitive and exploratory function, brain histopathology, and hepatic amyloid beta (Aβ) clearance in amyloid precursor protein/presenilin-1 double transgenic (APP/PS1) transgenic mice. Methods: Twenty-four six-month-old male APP/PS1 transgenic mice (body weight: 20–22 g) were used to establish the AD model. APP/PS1 transgenic mice were randomly assigned to one of the three groups: rest (AD group, n = 8), aerobic interval training (AIT group, n = 8), and aerobic continuous training (ACT group, n = 8). The exploration ability and anxiety of AD mice were measured using the open-field test. Learning and memory of AD mice were detected using the novel object recognition test, Y-maze test, and Morris water maze test. Neuronal damage was analyzed using hematoxylin and eosin staining and Nissl staining. Aβ deposition in the brain was detected using a thioflavin-S fluorescence assay and immunofluorescence. The mechanisms underlying hepatic Aβ clearance were investigated using an immunofluorescence assay and western blotting. Data were analyzed using one-way ANOVA with Tukey’s post hoc test, and p < 0.05 was deemed statistically significant. Results: The results revealed that both AIT and ACT improved the recognition memory and exploration ability of mice after 8 weeks of intervention. Additionally, both forms of aerobic exercise significantly mitigated neuronal damage and Aβ deposition in the brain and improved the hepatic clearance of Aβ. Conclusions: Our findings indicated that AIT and ACT can improve cognitive deficits in APP/PS1 mice, potentially by increasing the hepatic phagocytic capacity of Aβ. Hepatic clearance of Aβ may serve as a supplementary mechanism by which aerobic exercise can improve AD.